STUDY OF CONSUMER ACCEPTANCE OF PATIN FISH NUGGET (Pangasius hypophthalmus) WITH THE ADDITION OF NIPAH FRUIT FLOUR (Nypa futricans) - Rangkuti, Ahmad Kamil; Sari, N. Ira; Sumarto, Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
Abstract This study aims to determine consumer acceptance of catfish nuggets with the addition of nipah fruit flour and how much the addition of nipah fruit flour received by consumers. The treatments consisted of N1 (75 g tapioca flour), N2 (75 g nipa palm flour), N3 (25 g tapioca flour + 50 g nipa palm flour), N4 (50 g tapioca flour + 25 g nipa fruit flour). The analytical parameters observed were hedonic test (appearance, aroma, taste and texture) and chemical analysis (water, ash, protein, fat and crude fiber). The addition of 75 g nipa fruit flour was the best treatment preferred by panelists as many as 79 (98.75%) with the characteristics of bright yellow appearance, distinctive aroma of nipah fruit, a slight aroma of catfish, delicious and savory taste, taste of nipa fruit, dense texture, compact and chewy.Keywords: catfish nuggets, nipah fruit, organoleptic